1987
DOI: 10.1148/radiology.164.1.3588931
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic degenerative disk disease and spondylosis of the cervical spine: MR imaging.

Abstract: Evidence on magnetic resonance (MR) images of disk degeneration and herniation, as well as of cord and root impingement, may be regarded either as normal, age-related changes or as causative of symptoms. Individuals referred for MR examinations of the larynx without symptoms referable to the cervical spine were studied retrospectively (35 patients) or prospectively (65 patients) over a 2-year period. With a solenoid surface coil, 5-mm-thick sections were acquired in sagittal, axial, and coronal planes with T1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
136
0
10

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(151 citation statements)
references
References 0 publications
5
136
0
10
Order By: Relevance
“…A recent, comprehensive review determined that needle EMG has a sensitivity of 50-71% for subjects with neurological or radiological signs of a cervical radiculopathy, although the lack of a standardized gold standard may have resulted in an underestimation of this figure [7,8]. On the other hand, asymptomatic radiological abnormalities are commonly seen with advanced imaging studies [17,20,26,37,58]. It is well accepted that the diagnostic accuracy of specialized imaging is limited, especially with regards to foraminal nerve root impingement [11,15,38].…”
Section: Introductionmentioning
confidence: 99%
“…A recent, comprehensive review determined that needle EMG has a sensitivity of 50-71% for subjects with neurological or radiological signs of a cervical radiculopathy, although the lack of a standardized gold standard may have resulted in an underestimation of this figure [7,8]. On the other hand, asymptomatic radiological abnormalities are commonly seen with advanced imaging studies [17,20,26,37,58]. It is well accepted that the diagnostic accuracy of specialized imaging is limited, especially with regards to foraminal nerve root impingement [11,15,38].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic Resonance Imaging (MRI) is the imaging modality of choice [26] One study showed cord impingement in 16% of asymptomatic patients under age 64 years and in 26% of asymptomatic patients aged greater than 64 [27]. In those where MRI is contraindicated or not tolerated, contrastenhanced CT may be used which is just as useful in characterizing compression of the spinal cord.…”
Section: Investigationsmentioning
confidence: 99%
“…Cervical spondylotic myelopathy is the most common cause of cervical spinal cord dysfunction in individuals older than 55 [2]. By the age of 40, most will have degenerative changes evident on radiographs [3]. In fact, by age 60-65 years, 95% of asymptomatic men and 70% of asymptomatic women show degenerative changes on plain films [4].…”
Section: Introductionmentioning
confidence: 99%
“…By the age of 30, virtually all individuals will have at least microscopic degenerative changes in their cervical spine 2 .…”
Section: Introductionmentioning
confidence: 99%